At the Bench: Neutrophil extracellular traps (NETs) highlight novel aspects of innate immune system involvement in autoimmune diseases. Issue 2 (2nd October 2015) - Grayson, Peter C; Kaplan, Mariana J
Abstract : Basic Research Review for Clinicians: Immunogenic and vasculopathic roles of NETs in the pathogenesis of SLE and other related autoimmune diseases. Abstract: The putative role of neutrophils in host defense against pathogens is a well-recognized aspect of neutrophil function. The discovery of neutrophil extracellular traps has expanded the known range of neutrophil defense mechanisms and catalyzed a discipline of research focused upon ways in which neutrophils can shape the immunologic landscape of certain autoimmune diseases, including systemic lupus erythematosus. Enhanced neutrophil extracellular trap formation and impaired neutrophil extracellular trap clearance may contribute to immunogenicity in systemic lupus erythematosus and other autoimmune diseases by promoting the externalization of modified autoantigens, inducing synthesis of type I IFNs, stimulating the inflammasome, and activating both the classic and alternative pathways of the complement system. Vasculopathy is a central feature of many autoimmune diseases, and neutrophil extracellular traps may contribute directly to endothelial cell dysfunction, atherosclerotic plaque burden, and thrombosis. The elucidation of the subcellular events of neutrophil extracellular trap formation may generate novel, therapeutic strategies that target the innate immune system in autoimmune and vascular diseases.